Access Structures in a Standard Translation Dictionary - Louw, Phillip Adriaan (Lexikos, 1999)
The access structure is the primary guide structure in the central texts of any standard translation dictionary. The metalexicographical term "guide structures" refers to the set of structures that provides a framework within which the accessibility and availability of information types in the dictionary can be evaluated. The access structure is, however, not a singular entity. It includes certain substructures, of which the outer and inner access structures are the most important. In this article the status quo with regard to access structures in standard translation dictionaries with Afrikaans and English as treated language pair will be evaluated. Suggestions will then be made as to possible improvements. In the discussion of the outer access structure it is suggested that the rapid outer access structure be improved by using an elementary thumb index and that the current system of running heads be retained. For the standard outer access structure a better planned and motivated system of ordering homonyms, as well as a more consistent initial alphabetical ordering is suggested. The focus in the discussion of the inner access structure will be on improving the rapid inner access structure by an innovative use of typographical and non-typographical structural markers. Better systems of ordering information subtypes within information categories are suggested as an innovation in the standard inner access structure. Broad guidelines are therefore given to improve dictionary accessibility and enhance user-friendliness through improved access structures.Keywords: access structure; dictionary; dictionary accessibility; homonymy; inner access structure; inner search path; lexicography; metalexicography; outer access structure; outer search path; polysemy; rapid inner access structure; rapid outer access structure; standard inner access structure; standard outer access structure; standard translation dictionary; structural marker; user-friendliness